The solvent-free one-pot multicomponent tandem polymerization of 3, 4-dihydropyrimidin-2(1H)-ones (DHPMs) catalyzed by ionic-liquid@Fe3O4 NPs: the development of polyamide gels. Issue 8 (11th February 2021) - Kaur, Manpreet; Mayank,; Bains, Deepak; Singh, Gagandeep; Kaur, Navneet; Singh, Narinder
Abstract : Solvent-free MCTP via Biginelli DHPMs catalyzed by a non-toxic magnetic catalyst (IL1–2@ Fe3 O4 ) in a one-pot reaction was illustrated for the development of fluorescent non-conjugated polyamide gels. Abstract : The development of efficient multicomponent tandem polymerization (MCTP) has gained much interest recently. Herein, fluorescent non-conjugated polyamide gels are synthesized via Biginelli synthesis in one-pot under solvent free conditions using di-aldehyde and aliphatic di-amines in the presence of a newly developed magnetic catalyst (IL2@Fe3 O4 NPs). The formation of IL2@Fe3 O4 NPs (in which magnetic iron oxide NPs were coated with ionic liquid) was characterized via transmission electron microscopy (TEM), powder X-ray diffraction (PXRD), vibrating sample magnetometer (VSM), and Brunauer–Emmett–Teller (BET) studies. Polymerization in the presence of the new non-toxic magnetic catalyst proceeded smoothly, even at room temperature, giving high molecular weight ( M w up to 83 384 g mol −1 ) fluorescent polyamide gels in excellent yields with the easy removal of the magnetic catalyst from the reaction mixture. Thus, this approach showed great potential for being developed into a simple and efficient polymerization approach for obtaining structurally diversified, Biginelli 3, 4-dihydropyrimidin-2(1 H )-ones (DHPMs) in the polymer backbone. This overcomes the limitations of multicomponent polymerization, such as stoichiometric balance, low molecular weight, complicated workup procedures, and the poor solubility of polymeric products, and it also allows the easy removal of the catalyst. The structures of all the prepared polyamide gels were established using 1 H-NMR, 13 C-NMR, FT-IR spectroscopy and gel permeation chromatography (GPC) analysis. Moreover, thermogravimetric (TGA) analysis reveals that the newly designed magnetic catalyst (IL@Fe3 O4 NPs) possesses high thermal stability and can be reused, and it remains unchanged, even up to the tenth cycle of the MCTP reaction.